Influence of the wet-ear state on the outcomes of tympanic membrane repair under ear endoscopy: a prospective case-control study - Jun Zhang; Qinglin Bai; Na Zhao; Cong Li; Jia Yang (BMC Surgery)
Abstract Background To prospectively determine whether tympanoplasty for tympanic membrane perforation (TMP) in wet ears impacts recovery. Methods We prospectively enrolled 32 TMP patients (2021–2023) and divided them into the wet-ear (14 patients) and dry-ear groups (18 patients), according to the presence of middle-ear secretions/edema. All patients underwent high-resolution thin-slice computed tomography, ear endoscopy, and pure tone audiometry. Results Perforation healing was similar in the dry- ear (94.44%) and wet-ear groups (85.7%, P = 0.5685). At 3 months, dry ears were achieved in 94.44% and 92.86% of patients in the dry- and wet-ear groups, respectively (P > 0.05). The air-bone gap (ABG) at 3 months was similar in the dry-ear (9.4047 ± 4.3415 dB) and wet-ear groups (6.5278 ± 5.4552 dB, P = 0.1171). In both groups, the mean air-conduction threshold, bone-conduction threshold, and ABG significantly decreased postoperatively (P < 0.05). Conclusion Tympanoplasty for TMP in wet ears does not adversely affect healing.